1982
DOI: 10.1088/0031-8949/26/4/003
|View full text |Cite
|
Sign up to set email alerts
|

Pseudospin in Rotating Nuclear Potentials

Abstract: It is found that the concept of pseudo-spin and pseudo-oscillator quantum numbers, introduced by previous authors, can be helpful in understanding the qualitative features of quasiparticle motion in rotating potentials, for the orbits with normal panty (excluding the high j orbits). In the first part of the paper, the use of pseudo-spin in static deformed potentials is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
230
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(232 citation statements)
references
References 8 publications
(5 reference statements)
2
230
0
Order By: Relevance
“…For example, (n r s 1/2 , (n r −1)d 3/2 ) will havel = 1, (n r p 3/2 , (n r −1)f 5/2 ) will havel = 2, etc. This pseudospin symmetry has been used to explain features of deformed nuclei [3], including superdeformation [4] and identical bands [5,6] and to establish an effective shell-model coupling scheme [7]. In view of its central role in both spherical and deformed nuclei, there has been an intense effort to understand the origin of this symmetry.…”
mentioning
confidence: 99%
“…For example, (n r s 1/2 , (n r −1)d 3/2 ) will havel = 1, (n r p 3/2 , (n r −1)f 5/2 ) will havel = 2, etc. This pseudospin symmetry has been used to explain features of deformed nuclei [3], including superdeformation [4] and identical bands [5,6] and to establish an effective shell-model coupling scheme [7]. In view of its central role in both spherical and deformed nuclei, there has been an intense effort to understand the origin of this symmetry.…”
mentioning
confidence: 99%
“…The notion of pseudospins= 1/2 was defined [17,18] to elucidate this quasidegeneracy in view of nonrelativistic quantum mechanics.s (pseudospin) andl (pseudo-orbital angular momentum) concepts were introduced to define a pseudospin doublet with total angular momentum j =s+l . Identical bands, magnetic moment, deformation, and superdeformation in nuclei were successfully expounded by considering the pseudospin concept [19][20][21][22][23][24][25]. In spite of knowing that the pseudospin initially was a nonrelativistic concept, its relativistic characteristic was discovered [26]; Ginocchio reported that usual l of the lower part of the Dirac spinor corresponds to the pseudo-orbital angular momentum.…”
Section: Introductionmentioning
confidence: 99%
“…The pseudospin symmetry remains an important concept in the axially deformed [1,11,12,13] and even the triaxially deformed [14,15] nuclei. Based on this concept, a simple but useful pseudo-SU(3) model was proposed, and it was generalized to be the pseudo-symplectic model [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…One of the pioneering quantitative studies was carried out by Bohr, Hamamoto, and Mottelson [1] in 1982 in the scheme of rotating nuclear potentials. For the large deformation, the asymptotic Nilsson quantum numbers [N, n 3 , Λ]Ω are good quantum numbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation